Der Dietz Verlag (DDR) und seine China-Publikationen in den 1950er Jahren: Eine Untersuchung zur Publikations- und Übersetzungsgeschichte im Verlagsarchiv - Liu, Xiao (chronotopos – A Journal of Translation History, 2025)
The 1950s were a period of vibrant cultural exchange between the German Democratic Republic (GDR) and the People's Republic of China (PRC). Both countries belonged to the socialist camp, were founded almost simultaneously, and soon began a wide range of cultural cooperation. The Dietz Verlag in the GDR was the central publishing house of the Socialist Unity Party of Germany (SED) and had a particularly close connection to China-related topics during this period. It translated and published a series of books about China, including literary translations, reports, political writings, and the works of Mao Zedong, and established close cooperation with the Foreign Languages Publishing House Beijing and other publishers. This archival research focuses on how Dietz Verlag, through its network of writers, Soviet publications, and cultural agreements, managed to translate and publish books about China in East Germany despite limited Chinese language communication and translation resources.